Effect of Mycorrhizae Inoculation and Maggot Compost on Sunflower Development on Marginal Land - Obel Obel; Meisilva Erona (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2023)
The use of inorganic fertilizers for a long time has an adverse impact on soil quality and the environment. For this reason, an agricultural approach that uses potential natural resources is needed. One of them is by applying agriculture in an organic concept that utilizes biological materials such as mycorrhiza and the addition of maggot compost. The purpose of this study was to determine the effect of mycorrhizal inoculation and maggot compost on the development of sunflowers on marginal land. In practice, the study used a randomized block design consisting of two factors, namely mycorrhizal inoculum and maggot compost which was repeated 3 times. The results of the study showed that mycorrhizal inoculation and maggot compost had an influence on the development of sunflowers such as the time of full bloom, ribbon flower diameter, tube flower diameter, number of seeds planted and weight of 100 seeds on marginal land. the higher the dose of mycorrhiza and maggot compost applied, the increase in each parameter observed in sunflower development on marginal land.